2018
DOI: 10.1002/humu.23583
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of spliceogenic variants located in regions linked to high levels of alternative splicing:BRCA2c.7976+5G > T as a case study

Abstract: Many BRCA1 and BRCA2 (BRCA1/2) genetic variants have been studied at mRNA level and linked to hereditary breast and ovarian cancer due to splicing alteration. In silico tools are reliable when assessing variants located in consensus splice sites, but we may identify variants in complex genomic contexts for which bioinformatics is not precise enough. In this study, we characterize BRCA2 c.7976 + 5G > T variant located in intron 17 which has an atypical donor site (GC). This variant was identified in three unrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…In this context, minigenes represent a simple and robust tool to assay all potential splicing variants, since patient RNA samples are not always available. Actually, 260 BRCA1 / 2 variants have been so far tested by minigenes . Moreover, minigenes present some important advantages such as: (1) analysis of one single allele effect; (2) identification and quantification of all transcripts; (3) study of multiple DNA variants using just one multiple‐exon minigene; (4) assay in many cell types, essential for tissue‐specific alternative splicing; and (5) high reproducibility of physiological and pathological splicing patterns.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In this context, minigenes represent a simple and robust tool to assay all potential splicing variants, since patient RNA samples are not always available. Actually, 260 BRCA1 / 2 variants have been so far tested by minigenes . Moreover, minigenes present some important advantages such as: (1) analysis of one single allele effect; (2) identification and quantification of all transcripts; (3) study of multiple DNA variants using just one multiple‐exon minigene; (4) assay in many cell types, essential for tissue‐specific alternative splicing; and (5) high reproducibility of physiological and pathological splicing patterns.…”
Section: Discussionsupporting
confidence: 75%
“…Previous results from our group showed that minigene tests of at least 16 different BRCA2 variants from exons 17 to 27 reproduced patient RNA outcomes . Moreover, the reproducibility of MGBR2_2–9 splicing outcomes was supported by previous studies based on patient RNA or minigene data, according to which fourteen variants matched preceding results: c.67+3A>G, c.68‐7T>A, c.316+3del, c.316+5G>C, c.426‐12_426‐8del, c.467A>G, c.516+ 1G>T, c.517G>T, c.572A>G, c.617C>G, c.627C>A/T, c.631G>A, c.631+3A>G and c.681+4A>G .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The minigene MGBR2_14-20 had previously been used to study variants of exons 16, 17, and 18, proving that it is a reliable and robust tool to functionally assay splicing variants (Fraile-Bethencourt et al, 2017, 2018; Montalban et al, 2018). The MGBR2_14-20 is a 10.7 Kb construct which, after transfection in MCF-7 cells, produces a transcript with the following structure: V1-BRCA2_exons from 14 to 20-V2 (1,806 nt) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study reported that variants affecting splicing, namely spliceogenic, are the third most common type occurring in BRCA1 and BRCA2 genes, accounting for 10.1% and 7.6% of the total, respectively (Rebbeck et al, ). Although multiple spliceogenic variants producing abnormal transcripts have been identified in HBOC families, the clinical relevance of the splicing outcomes can be sometimes difficult to determine (de Caputo et al, ; Colombo et al, ; la Hoya et al, ; Montalban et al, ). Furthermore, numerous BRCA1/2 alternative splicing events have been described in several tissues and cell lines, adding complexity to the interpretation of splicing outcomes generated from variant alleles (Colombo et al, ; Fackenthal et al, ).…”
Section: Introductionmentioning
confidence: 99%